Polymorphism of rs873308 near the transmembrane protein 57 gene is associated with serum lipid levels. Issue 2 (14th March 2014) - Guo, Tao; Yin, Rui-Xing; Lin, Quan-Zhen; Wu, Jian; Shen, Shao-Wen; Sun, Jia-Qi; Shi, Guang-Yuan; Wu, Jin-Zhen; Li, Hui; Wang, Yi-Ming
Abstract : SNP (single-nucleotide polymorphism) of rs10903129 near the TMEM (transmembrane protein) 57 locus has been associated with TC (total cholesterol) in a previous GWAS (genome-wide association study), but the association of TMEM57 rs873308 SNP and serum lipid levels has not been previously reported. The current study was undertaken to detect the association of the TMEM57 rs873308 SNP and several environmental factors with serum lipid profiles in the Han Chinese and Mulao populations. The genotypes of the TMEM57 rs873308 SNP in 865 individuals of Han Chinese and 902 participants of Mulao nationality were determined by PCR and RFLP (restriction-fragment-length polymorphism) combined with gel electrophoresis and then confirmed by direct sequencing. The T allele frequency of TMEM57 rs873308 SNP was not different between Han and Mulao (23.18% versus 25.72%, P >0.05), but different between males and females in the two ethnic groups ( P <0.05). The T allele carriers had lower serum TC, Apo (apolipoprotein) B, HDL-C (high-density lipoprotein cholesterol) levels, ApoA1/ApoB ratio in Han; and lower TAG (triacylglycerol), LDL-C (low-density lipoprotein cholesterol), ApoA1 levels and the ApoA1/ApoB ratio and higher HDL-C levels in Mulao than the T allele non-carriers. There was also different association of the TMEM57 rs873308 SNP and serum lipid profiles between males and females in the both ethnic groups. Serum lipid parameters in the two ethnic groups were also associated with several environmental factors. The association of the TMEM57 rs873308 SNP and serum lipid levels was different in the Han Chinese and Mulao populations and between males and females in the both ethnic groups. There may be a sex-specific association of the TMEM57 rs873308 SNP and serum lipid levels in our study populations.